The populist parties and their electoral success: different causes behind different populisms? The case of the Five-star Movement and the League. Issue 3 (3rd July 2019) - Caiani, Manuela
ABSTRACT: In this article, we focus on the reasons for the success of the populist parties in Italy, relating them to the political, economic and cultural–migration crises and to the role played by these crises in the political discourse of the two populist parties currently in office in the country: the Movimento Cinque Stelle (Five-star Movement, M5s) and the League. The article underlines the importance of the distinction between different types of populism (in terms of their main aims and the main driving forces behind them) and the ways in which they complement one another. It also considers the tensions that exist between them when diagnosing the country's problems and when drawing up proposals to tackle them, as well as identifying the people – voters – whose support they each seek to attract. The discussion will end by suggesting that the frame of reference provided by the comparative literature remains relevant and useful as a means of understanding internal politics in Italy, with an emphasis on the importance of the 'construction' of the crisis (or crises) by the various actors.